Mechanical and Postfire Structural Performances of Concrete under Elevated Temperatures - Vishal Murugan; Alireza Bahrami; Rakshit Srivastava; K. S. Satyanarayanan; Prakash Murugan; J. S. Arvind (Civil Engineering Journal, 2023)
This article investigates the mechanical and postfire structural performances of concrete under elevated temperatures (200°C, 400°C, 600°C, and 800°C) after 7 and 28 days of concrete curing. The main objective of this study is to evaluate the post-fire behavior of concrete structures and how their modulus of elasticity values influence their structural parameters. Mechanical studies, namely, the compressive strength, splitting tensile strength, and flexural strength, were performed on cubes, cylinders, and prism beams under normal and elevated temperatures. Non-destructive tests, like rebound hammer and ultrasonic pulse velocity, were also conducted on concrete cubes to obtain the strength of concrete before and after heating the specimens. Microstructural studies, in particular, scanning electron microscope and energy dispersive x-ray spectroscopy, were done to analyze the changes in the chemical composition of concrete under the effect of the temperatures. The weight loss of the concrete specimens was assessed under the elevated temperatures. The results indicated that the geometric shapes of the specimens influenced the loss in the moisture content of concrete under an elevated temperature scenario. Microstructural studies revealed the changes in the chemical composition under the elevated temperatures. The results of this research can be further integrated for industrial applications. Doi: 10.28991/CEJ-2023-09-08-04 Full Text: PDF